1994
DOI: 10.1063/1.112724
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline structure of AlGaN epitaxy on sapphire using AlN buffer layers

Abstract: The crystalline structure near the substrate interface has been studied for AlGaN films grown on (0001) sapphire substrates by metalorganic chemical vapor deposition, using AlN buffer layers. Transmission electron lattice images show that the sapphire/AlN interface is coherent, with misfit dislocations separated by 2.0 nm, corresponding to relaxed bulk lattice parameters. The interface between the buffer layer and the AlGaN film is discussed. The defect structure of the epilayer near the substrate interface co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(49 citation statements)
references
References 5 publications
1
47
0
1
Order By: Relevance
“…It is well known that such large lattice misfits in a hexagonal heteroepitaxial system, for example, ZnO/Al 2 O 3 , GaN (or AlN)/Al 2 O 3 , etc., typically yield the heterostructures of (0001) [11 20] overlayer ║(0001) [10 10] substrate , whose overlayer is crystallographically rotated by 30°with respect to the substrate to minimize dangling bond density through covalent heteroepitaxy. [32][33][34] Recent works on epitaxy of III-V nanowires on graphene also discussed the possible rotated in-plane epitaxial relationships or different nanowire growth directions presumably caused by lattice mismatch when covalent epitaxial links exist at the heterointerface. 35,36 Hence, it is strongly suggested that the observed domain-aligned heteroepitaxial relationship of ZnO/hBN should result from weakly bound vdW heterointerfaces.…”
Section: Epitaxy Of Zno Nanostructures On Hbn H Oh Et Almentioning
confidence: 99%
“…It is well known that such large lattice misfits in a hexagonal heteroepitaxial system, for example, ZnO/Al 2 O 3 , GaN (or AlN)/Al 2 O 3 , etc., typically yield the heterostructures of (0001) [11 20] overlayer ║(0001) [10 10] substrate , whose overlayer is crystallographically rotated by 30°with respect to the substrate to minimize dangling bond density through covalent heteroepitaxy. [32][33][34] Recent works on epitaxy of III-V nanowires on graphene also discussed the possible rotated in-plane epitaxial relationships or different nanowire growth directions presumably caused by lattice mismatch when covalent epitaxial links exist at the heterointerface. 35,36 Hence, it is strongly suggested that the observed domain-aligned heteroepitaxial relationship of ZnO/hBN should result from weakly bound vdW heterointerfaces.…”
Section: Epitaxy Of Zno Nanostructures On Hbn H Oh Et Almentioning
confidence: 99%
“…The films often are composed of crystallites highly oriented in the c direction. [7][8][9]15 Their misorientation relative to each other is usually so small, < 1°, 7 that the film is often said to be a single crystal containing a large number of defects frequently designated as stacking AlN films deposited on SiC or sapphire substrates by pulsed laser deposition were annealed at 1200°C, 1400°C, and 1600°C for 30 min in an inert atmosphere to examine how their structure, surface morphology, and substrate-film interface are altered during high temperature thermal processing. Shifts in the x-ray rocking curve peaks suggest that annealing increases the film density or relaxes the films and reduces the c-axis Poisson compression.…”
Section: Introductionmentioning
confidence: 99%
“…AlN films have been used as encapsulates for annealing ion implanted SiC films, 1-3 a buffer layer for growing GaN films on sapphire [4][5][6][7][8] or SiC, 9 an insulating dielectric, [10][11][12] and as a thin film resonator. 13 They have been deposited by pulsed laser deposition (PLD), [14][15][16][17] organometallic vapor phase epitaxy (OMVPE), [4][5][6][7][8][9][10][11]18 molecular beam epitaxy (MBE), 19,20 chemical vapor deposition (CVD), 21,22 and reactive ion sputtering 23-26 on a variety of substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5]. AlN films can be grown on sapphire by metal organic chemical vapor deposition [6,7] or molecular beam epitaxy [8][9][10] at high growth temperature. The crystalline quality of AlN films is deteriorated by threading dislocations which usually originate from the large lattice mismatch and * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%